2020
DOI: 10.1371/journal.pone.0231966
|View full text |Cite|
|
Sign up to set email alerts
|

Conjunctivitis, the key clinical characteristic of adult rubella in Japan during two large outbreaks, 2012–2013 and 2018–2019

Abstract: Background Rubella virus infection mainly causes illness with mild fever, rash, and lymphadenopathy in children; however, the clinical characteristics of adult rubella are not well-known. Methods An observational study was conducted to compare the characteristics between adult rubella and adult non-rubella among participants aged �18 years, with suspected symptomatic rubella. Participants were screened for rubella-specific IgM expression using an enzyme immune assay kit, at a tertiary care hospital in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Furthermore, for both CMV and rubella virus infections, infants presenting with systemic, symptomatic infection reflecting disseminated infection are more likely to progress to severe or profound hearing loss [ 76 , 77 ]. Notably, CMV and rubella virus infection acquired postnatally have not been found to cause hearing loss [ 78 , 79 ], suggesting that prenatal cochlear development is particularly sensitive. Importantly, different congenital infections also appear to cause hearing loss via disparate mechanisms.…”
Section: The Cochlea As a Model Organ To Study The Effect Of Early Life Inflammation On The Developing Hematopoietic And Immune Systemsmentioning
confidence: 99%
“…Furthermore, for both CMV and rubella virus infections, infants presenting with systemic, symptomatic infection reflecting disseminated infection are more likely to progress to severe or profound hearing loss [ 76 , 77 ]. Notably, CMV and rubella virus infection acquired postnatally have not been found to cause hearing loss [ 78 , 79 ], suggesting that prenatal cochlear development is particularly sensitive. Importantly, different congenital infections also appear to cause hearing loss via disparate mechanisms.…”
Section: The Cochlea As a Model Organ To Study The Effect Of Early Life Inflammation On The Developing Hematopoietic And Immune Systemsmentioning
confidence: 99%
“…Recently, Nomoto et al reported that conjunctivitis was significantly associated with adult rubella in Japan. Although it might be useful for the early diagnosis of adult rubella, the time of its appearance was not described [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…36 Recently, Japan endured two outbreaks of rubella in 2012–2013 and 2018–2019. 7 The majority of patients were men, aged ≥40 years, and ineligible for national routine vaccination. Vaccines for mumps among children are not routine, but voluntary in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Cluster infections of varicella among foreigners were reported between 2012 and 2016. 6 Rubella outbreaks occurred recently among unvaccinated populations in Japan, 7 and two international students were diagnosed with this disease in 2019, which resulted in cluster infections in their school. 8 Furthermore, there was a report of an outbreak of rubella among foreign trainees undergoing vocational training in 2016.…”
Section: Introductionmentioning
confidence: 99%